Bahasa InEvaluasi Daya Dukung Perairan Untuk Akuakultur : Studi Kasus Berbagai Negaradonesia - Taufanputri, Melati; Hasan, Zahidah; Herawati, Heti (Jurnal Perikanan Unram, 2025)
Carrying capacity of aquatic ecosystems is a crucial concept in ensuring the sustainability of these ecosystems amidst increasing human activities, particularly intensive aquaculture. This study aims to review the literature on aquatic carrying capacity, focusing on the methods and parameters used in related research and the implications of these findings for environmental management. Using a literature study approach, several journals related to the aspects of aquatic carrying capacity were collected and analyzed. The review indicates that factors such as water quality, types of macrophytes used to control eutrophication, and aquaculture management techniques significantly influence the carrying capacity of aquatic systems. A comprehensive understanding of aquatic carrying capacity is essential for developing effective and sustainable management policies.